7TH GRADE COURSE” NATURAL GEOGRAPHY OF MATERIALS AND OCEANS “USING THE” DATING " TRAINING ON THE TOPIC OF THE NATURE ZONES OF EURASIA - Arabboyev Asliddin Rafikzhan Ogli; Foziljonov Zuhriddin Abdumajid Ogli (Scholar Express Journals, 2023)
In this article, the 7th grade course “natural geography of materials and oceans” is mentioned, giving several methodological recommendations on the use of the “dating” training on the topic of the nature zones of Eurasia. As a result of the application of this method, the school provides a special service for strengthening both theoretical and practical knowledge of students, in the development of such characteristics as creativity, traceability
Keywords: information; skill; method of Education